Nuclear Receptors in the Control of the NLRP3 Inflammasome Pathway - Duez, Hélène; Pourcet, Benoit (Frontiers in Endocrinology, 2021)
The innate immune system is the first line of defense specialized in the clearing of invaders whether it is foreign elements like microbes or self-elements that accumulate abnormally including cellular debris. Inflammasomes are master regulators of the innate immune system, especially macrophages, and key sensors involved in maintaining cellular health in response to cytologic pathogens or stress signals. Inflammasomes are cytoplasmic complexes typically composed of a sensor molecule such as NOD-Like Receptors (NLRs), an adaptor protein including ASC and an effector protein such as pro-caspase 1. Upon stimulation, inflammasome complex components are associated to process the cleavage of the pro-caspase 1 and the subsequent activation of pro-inflammatory cytokine including IL-18 and IL-1β. Deficiency or overactivation of such important sensors leads to critical diseases including Alzheimer diseases, chronic inflammatory diseases, cancers, acute liver diseases and cardiometabolic diseases. Inflammasomes are tightly controlled by a two-step activation regulatory process consisting in a priming step, which activates the transcription of inflammasome components; and an activation step which leads to the inflammasome complex formation and the subsequent cleavage of pro-IL1 cytokines. Apart from NF-κB pathway, nuclear receptors have recently been proposed as an alternative regulatory pathway. This review will discuss the role of nuclear receptors in the control of NLRP3 inflammasome and the putative beneficial effect of new modulators of inflammasomes in the treatment of inflammatory diseases including colitis, fulminant hepatitis, cardiac ischemia-reperfusion and neural diseases.